Role of inflammatory mediators, macrophages, and neutrophils in glioma maintenance and progression: mechanistic understanding and potential therapeutic applications - Basheer, Abdul Samad; Abas, Faridah; Othman, Iekhsan; Naidu, Rakesh (MDPI AG, 2021)
Gliomas are the most common, highly malignant, and deadliest forms of brain tumors. These intra-cranial solid tumors are comprised of both cancerous and non-cancerous cells, which contribute to tumor development, progression, and resistance to the therapeutic regimen. A variety of soluble inflammatory mediators (e.g., cytokines, chemokines, and chemotactic factors) are secreted by these cells, which help in creating an inflammatory microenvironment and contribute to the various stages of cancer development, maintenance, and progression. The major tumor infiltrating immune cells of the tumor microenvironment include TAMs and TANs, which are either recruited peripherally or present as brain-resident macrophages (microglia) and support stroma for cancer cell expansion and invasion. These cells are highly plastic in nature and can be polarized into different phenotypes depending upon different types of stimuli. During neuroinflammation, glioma cells interact with TAMs and TANs, facilitating tumor cell proliferation, survival, and migration. Targeting inflammatory mediators along with the reprogramming of TAMs and TANs could be of great importance in glioma treatment and may delay disease progression. In addition, an inhibition of the key signaling pathways such as NF-κB, JAK/STAT, MAPK, PI3K/Akt/mTOR, and TLRs, which are activated during neuroinflammation and have an oncogenic role in glioblastoma (GBM), can exert more pronounced anti-glioma effects.